2019
DOI: 10.1111/hepr.13336
|View full text |Cite
|
Sign up to set email alerts
|

Intraprocedural computed tomography/magnetic resonance–contrast‐enhanced ultrasound fusion imaging improved thermal ablation effect of hepatocellular carcinoma: Comparison with conventional ultrasound

Abstract: Aim To retrospectively compare the treatment effect of intraprocedural computed tomography/magnetic resonance–contrast‐enhanced ultrasound (CT/MR‐CEUS) fusion imaging (FI) with that of conventional ultrasound (US) in the guidance and assessment of thermal ablation of hepatocellular carcinoma (HCC). Methods The FI group (112 patients with 129 HCC) was treated between April 2010 and December 2012, whereas the US group (83 patients with 90 HCC) was treated between January 2008 and March 2010. Either CT/MR‐CEUS FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 45 publications
(93 reference statements)
1
32
1
Order By: Relevance
“…Moreover, subgroup analysis, based on mean diameter (<15 mm) revealed no heterogeneity (I 2 = 0.0%, p = 0.77). Results of sensitivity analysis, used to examine the effect of each study on pooled effect diameter, revealed that exclusion of Ma's study (21) from the analysis altered the overall effect diameter (RR, RE:1; 95% CI: 0.99, 1.02, p = 0.84). Moreover, no evidence of significant publication bias was found across the included studies with regards to technical efficiency (p = 0.81, Begg's test and p = 0.65, Egger's test).…”
Section: Effect On Technical Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, subgroup analysis, based on mean diameter (<15 mm) revealed no heterogeneity (I 2 = 0.0%, p = 0.77). Results of sensitivity analysis, used to examine the effect of each study on pooled effect diameter, revealed that exclusion of Ma's study (21) from the analysis altered the overall effect diameter (RR, RE:1; 95% CI: 0.99, 1.02, p = 0.84). Moreover, no evidence of significant publication bias was found across the included studies with regards to technical efficiency (p = 0.81, Begg's test and p = 0.65, Egger's test).…”
Section: Effect On Technical Efficiencymentioning
confidence: 99%
“…However, published studies have yielded conflicting results with regards to efficacy and safety of FI relative to that of ultrasound. While some studies have shown that FI is more superior than ultrasound (20,21), others have found no significant differences in the two technologies (22,23). Therefore, the present metaanalysis was designed to systematically evaluate efficacy and safety of FI relative to ultrasound in radiofrequency surgery for the treatment of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow the clinicians to immediately assess the treatment response post-procedure and perform immediate supplementary ablation if needed. This potentially avoids the need for secondary treatment as well as reducing the economic burden to the patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fusion imaging combining CEUS and hepatobiliary-phase CEMRI also appears to be useful for evaluating the therapeutic efficacy of RFA for HCCs identified as having isoechoic or unclear margins by conventional US [12]. The usefulness of fusion imaging combining CEUS and CECT/CEMRI for evaluating the therapeutic efficacy of RFA has been reported by several investigators [13,14]. The reported concordance rate for the results of the RFA efficacy evaluation between intraprocedural CEUS and CECT/CEMRI fusion imaging and CECT/CEMRI performed within 30 days after RFA was 91.1% (72/79) [13].…”
mentioning
confidence: 97%